La economía digital bajo un modelo de bienes públicos: revisión de estretegias conductuales para incrementar la confianza - Acevedo Campos, David (2019)
Digital economy is full of challenges, especially about its acceptance in different sets of the population. Although is widely accepted between youngsters, older generations are more reluctant to participate on it due to a bad trust perception of buying products and services online. This paper summarizes some researches about the development of trust and the associated risk of a digital market. For example, how the communication channel can enhance the cooperation when is face to face, compared to a less personal channel like chat messages. Therefore, is a priority to explore the mechanisms which determine how trust is developed between customers and merchants, just like the participation of an intermediary who looks after both payment and product of a transaction, or the use of better security systems which make payments harder to hack. Under these considerations, the objective of this paper is to sum up some theoretical and experimental contributions of behavioral science on the development of trust in a digital environment, as well as some strategies used till the date.